A baseline study of coastal water quality in the Lembeh Strait of North Sulawesi, Indonesia, in 2013. Issue 1 (15th March 2016) - Baohong, Chen; Muchtar, Muswerry; Tingting, Fu; Hongzhe, Chen; Jigang, Wang; Kaiwen, Zhou; Jianguo, Du; Hui, Lin; Bin, Chen
Abstract: The concentrations of nutrients (NO2 –N, NO3 –N, NH4 –N, PO4 –P, and SiO3 –Si) and their ratios in the Lembeh Strait were estimated in April 2013, off the northeastern coast of Sulawesi in Indonesia. The concentrations of dissolved inorganic nitrogen (DIN) (NO2 –N + NO3 –N + NH4 –N) and PO4 –P were low, with a maximum of 0.181 and 0.007 mg/L, respectively. P was found to be the limiting factor controlling phytoplankton growth overall. According to a potential eutrophication assessment model, both the surface water and the water at a depth of 15 m were classified as water 1 (poor nutrition). This study provides baseline information including chemical datasets for future pollution monitoring and management programs in this area. Highlights: The spatial distribution of nutrient concentration and mol ratios in the Lembeh Strait was studied. P was found to be the limiting factor in phytoplankton growth compared to N and Si in general. The eutrophication status of the strait was level 1 (poor nutrition).